Acquisition algorithm for BOC signals in high dynamic environment - Yi PAN; Tianqi ZHANG; Gang ZHANG; Baoze MA (Tongxin xuebao)
As the synchronization of binary offset carrier (BOC) signals couldn’t be realized in high dynamic environment by traditional acquisition algorithms,an acquisition algorithm based on fractional Fourier transform (FRFT) and discrete polynomial-phase transform (DPT) was proposed.Firstly,the algorithm determined how to process the received signal according to the dynamic order obtained by the order operation.And then the acquisition was achieved by searching the spectral peak of the FRFT algorithm to obtain the estimation of dynamic parameters and code phase.Theoretical analysis and simulations show that the proposed algorithm eliminates the influence of second-order doppler shift rate based on original FRFT acquisition algorithm,which can successfully capture high dynamic BOC signals.The proposed algorithm further enhances the dynamic adaptability and anti-noise performance and has superior performance in detection probability and acquisition time in comparison with other algorithms.